2012
DOI: 10.1103/physrevc.86.025801
|View full text |Cite
|
Sign up to set email alerts
|

Level structure of18Ne and its importance in the14O(α,p

Abstract: The level structure of 18 Ne above the α-decay threshold has been studied using the 16 O( 3 He,n) reaction. A coincidence measurement of neutrons and charged particles decaying from populated states in 18 Ne has been made. Decay branching ratios were measured for six resonances and used to calculate the 14 O(α,p) 17 F reaction rate which is a measure of one of two breakout paths from the Hot CNO cycle. The new experimental information combined with previous experimental and theoretical information provides a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…6 in Ref. [39]). As discussed above, such a state at E x = 6.85 ± 0.10 MeV was also observed in the present work.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…6 in Ref. [39]). As discussed above, such a state at E x = 6.85 ± 0.10 MeV was also observed in the present work.…”
mentioning
confidence: 91%
“…Because no such state was previously observed in 18 Ne, Notani et al [32] speculated that it might be due to a state at E x ∼ 7.1 MeV decaying to the first excited state of 17 F. Later, a careful 17 F+p scattering experiment [30] was performed, but no evidence of inelastic 17 F+p scattering was observed in this energy region, and the decay branching ratio to the first excited state ( p / p ) was constrained to be <0.03. Almaraz-Calderon et al [39] recently reported a ratio of 0.19 ± 0.08 for the 7.05 MeV state. Later, this large ratio was questioned by Fortune [40] who estimated a ratio less than about 2 × 10 −4 , in agreement with an earlier limit of 1/90 from Harss et al [35].…”
mentioning
confidence: 95%
See 3 more Smart Citations